Table of Content - - (Journal of Humanities & Social Sciences, 2025)
Table of Content: The scientific life of the city of Levantine Tripoli during the nineteenth century AD Mr. Abdallah Samir Dannoun Children in Difficult Situations: Between the Challenges of Reality and the Possibilities of Integration Sociological study/Guercif -Morocco- Dr. Abdelillah Douz Learning Difficulties and their Realtionship with Family Systems(Bent Jbail region-southern Lebanon 2018) Mr. Daoud Ali Faraj Family in search of a treatment: Example of Families facing infertility in the city of Tetouan, northern Morocco (2023–2024) Asst-Prof. Mohamed Ahmed NFIFAKH The Impact of Overlooking the Social Dimension in Urban Projects on Citizens’ Behavior Toward Public Property: A Case Study of Kenitra City Mr. Mohamed EL Mestari, Dr. Mbarek Tayii Traditional Tanning Craft in Buraidah City during (1322-1402AH/1904-1982AD) Mr. Abdulkarim Mohammad Alseadoon,Co-Prof. Soliman Mohammed Al-Atni